A comparative safety review between GLP-1 receptor agonists and SGLT2 inhibitors for diabetes treatment. Issue 3 (4th March 2018) - Consoli, Agostino; Formoso, Gloria; Baldassarre, Maria Pompea Antonia; Febo, Fabrizio
ABSTRACT: Introduction : Glucagon-like peptide-1 receptor agonists (GLP-1RA) and sodium glucose cotransporter 2 inhibitors (SGLT2i) are of particular interest in type 2 diabetes treatment strategies, due to their efficacy in reducing HbA1c with a low risk of hypoglycaemia, to their positive effects on body weight and blood pressure and in light of their effects on cardiovascular risk and on nephroprotection emerged from the most recent cardiovascular outcome trials. Since it is therefore very likely that GLP-1RA and SGLT2i use will become more and more common, it is more and more important to gather and discuss information about their safety profile. Area Covered : adverse events and the safety concerns most often emerged in trials with GLP-1RA namely, exenatide long acting release (LAR), dulaglutide, liraglutide, semaglutide, lixisenatide or SGLT2i, namely empagliflozin, dapagliflozin, canagliflozin and SGLT2i with an attempt at comparing the safety profiles of molecules of these two classes. Expert opinion : GLP-1RA and SGLT2i, although each associated with different specific side effects, share a 'similar' safety profile and are both drugs relatively easy to handle. The potentially complementary mechanisms of action, the cardio and nephroprotective effects demonstrated by molecules of both classes, make these drugs potentially useful even in add on to each other.